If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9 = x + -18 Reorder the terms: 9 + 4x = x + -18 Reorder the terms: 9 + 4x = -18 + x Solving 9 + 4x = -18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 4x + -1x = -18 + x + -1x Combine like terms: 4x + -1x = 3x 9 + 3x = -18 + x + -1x Combine like terms: x + -1x = 0 9 + 3x = -18 + 0 9 + 3x = -18 Add '-9' to each side of the equation. 9 + -9 + 3x = -18 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = -18 + -9 3x = -18 + -9 Combine like terms: -18 + -9 = -27 3x = -27 Divide each side by '3'. x = -9 Simplifying x = -9
| 6t+2(4t+5)= | | 405=80n-25 | | 4.5-2k=6 | | 5+9(2+7j)= | | 6b+19=25 | | .5(16-x)=-12(x+7) | | 4x-7=4(x+5) | | X-8-1=3+4k+k | | -2x=2-(-10) | | X+.6*x=159 | | 1.72x+x=6 | | 4timesx=56 | | 3h-13=-11 | | x-1=sqrt(15-7x) | | 6=-6+48 | | 365=T+-217 | | s-15=15.53 | | 7b^2+23b+6= | | -5c-10-5c=8 | | 5(-9-4x)+10(1+10)= | | -4x-5(2x-y)-3y= | | 0.8x-11=0.34x+41 | | 2+9x=x+18 | | 3x-6+x=-25 | | 4n-40=4(n-8)+2n | | -5(-2x-13)-7x= | | 6=-6(1n-8) | | 5n+39=4(8n+3) | | 6=8.15 | | -8(z+5)+3z= | | m^2-12m+35= | | 30x-140-23x= |